Contact problem tensely – the deformed condition of bodies at work of the steel pulleys and the cable - Попов, А.П.; Бутаков, Б.И.; Марченко, Д.Д. (Problems of Tribology, 2014)
In this paper we solve the contact problem is intense - deformed bodies, an example of the steel pulleys and ropes, whose decision is based on the new methodology of theoretical studies of contact strength elastic compression halfspaces bounded by curved surfaces with respect to the initial linear interaction of bodies.